Simulation of heat transfer processes in cooling systems with heat recovery. (November 2019) - Sinitsyn, Anton; Rakov, Vyacheslav; Eperin, A P; Rundygin, Yu A; Rusinov, R V; Izmailov, R A; Simonov, A M; Yun, V K; Mihin, Anton; Akhmetova, Irina
Abstract: The article considers modeling of modern heat exchange systems which use thermal energy for its beneficial use. The proposed mathematical model makes it possible to investigate systems with utilization of thermal energy. The article presents the results of simulation of heat exchange processes using heat energy recovery for internal combustion engines.